Unusual Forehead Tremor in Four Patients with Essential Tremor. (17th July 2012) - Gascón-Bayarri, Jordi; Campdelacreu, Jaume; Calopa, Màtil; Jaumà, Serge; Bau, Laura; Povedano, Mònica; Montero, Jordi
Abstract : Forehead tremor has only been reported in two patients with essential tremor, one with rhythmic tremor and the other with dystonic tremor. We report 4 new patients with essential tremor who present a 4–6 Hz frontal tremor registered by electromyography and unusual features like frontal tremor preceding limb tremor or unilateral involvement. Frontal tremor is present in some patients with essential tremor, sometimes preceding limb tremor. Treatment with botulinum toxin may be useful.